χάρις: Ketika Pemberian Ditanggapi dengan Rasa Syukur (Membaca Kisah Paulus dan Lidia dalam Kis. 16:13-15 melalui Lensa Gift of Exchange Repertoire): χάρις: When a Gift is Reciprocated by Gratitude (Reading the Encounter of Paul and Lidya in Acts 16:13-15 through the Lens of Gifts of Exchange Repertoire - Loba, Klementius Anselmus; Antonius Galih Arga Wiwin, Aryanto (DISKURSUS - JURNAL FILSAFAT DAN TEOLOGI STF DRIYARKARA, 2024)
This article analyzes the encounter story of Paul and Lydia (Acts 16:13-15) as a concrete example of the practice of reciprocal gift exchange. The exchange of “gifts” between the two took place when Paul preached the Christian faith and baptized Lydia, and she reciprocated by giving Paul a ride. This study employs a social science approach by taking a repertoire of gift exchanges from the ancient Greco-Roman world to be applied to this story, and biblical studies for interpretation. From the repertoire of exchanges available, we chose χάρις to apply to this story. The concept of χάρις reflects a reciprocal exchange that involves two actions at once, namely the giving of a “gift” and the receiving of it with gratitude in return. The reciprocal gift exchange between Paul and Lydia shows that a gift demands a response (reciprocity). However, the reciprocal exchange between the two was not exploitative, as it took place within the framework of Christ’s χάρις. Through the gift of Christ’s χάρις, they concretely share χάρις with one another. In this context, Paul and Lydia not only demonstrated their identity as followers of Christ but also strengthened their bonds as brothers and sisters. Abstrak Artikel ini menganalisa kisah pertemuan Paulus dan Lidia (Kis. 16:13-15) sebagai sebuah contoh konkret dari praktik pertukaran hadiah atau pemberian timbal balik. Pertukaran “hadiah” antara keduanya terjadi ketika Paulus mengajarkan iman Kristen dan membaptis Lidia, dan Lidia membalasnya dengan memberikan tumpangan kepada Paulus. Studi ini menggunakan pendekatan ilmu sosial dengan memakai repertoar pertukaran hadiah atau pemberian timbal balik dari tradisi dunia Yunani-Romawi kuno untuk diterapkan dalam penafsiran biblis. Dari repertoar pertukaran yang tersedia, studi ini memilih χάρις untuk diterapkan dalam kisah tersebut. Konsep χάρις mencerminkan pertukaran timbal balik yang melibatkan dua tindakan sekaligus, yakni pemberian “hadiah” dan penerimaan dengan rasa syukur sebagai balasannya. Pertukaran hadiah timbal balik antara Paulus dan Lidia menunjukkan bahwa sejatinya sebuah pemberian menuntut tanggapan (resiprositas). Namun pertukaran timbal balik antara keduanya tidak bersifat eksploitatif, karena terjadi dalam bingkai χάρις Kristus. Melalui pemberian χάρις Kristus, mereka secara konkret berbagi χάρις terhadap satu sama lain. Dalam konteks ini, Paulus dan Lidia tidak hanya menunjukkan identitas mereka sebagai pengikut Kristus, tetapi juga memperkuat ikatan mereka sebagai saudara seiman. Kata-kata kunci: Paul, Lidya, χάρις, pertukaran timbal-balik, Kis 16: 13-15, budaya Yunani-Romawi